Assessment of Genetic Relationships in Breeding Lines and Cultivars of Brassica napus and Their Implications for Breeding Winter Oilseed Rape. Issue 4 (1st July 2016) - Liersch, Alina; Bocianowski, Jan; Woś, Henryk; Szała, Laurencja; Sosnowska, Katarzyna; Cegielska‐Taras, Teresa; Nowosad, Kamila; Bartkowiak‐Broda, Iwona
Abstract : The level of genetic diversity or similarity between parents has been proposed as a predictor of F1 generation performance and heterosis for seed yield. The objective of this study was to determine the feasibility of using amplified fragment length polymorphism (AFLP) fluorescent‐labeled primers to evaluate the genetic relationships between 101 oilseed rape ( Brassica napus L.) genotypes to maximize the selection of different parents in a breeding program. The collection of genotypes included 25 cytoplasmic male sterility ogura and 21 restorer lines ( Rfo ). The set of genotypes was completed with B . napus cultivars of Polish, European, and Asian origin and resynthesized lines. Ten primer‐enzyme combinations ( Eco RI and Mse I) were used. Genetic similarities among genotypes were estimated in accordance with the Nei and Li coefficient of similarity, and then the unweighted pair group method using arithmetic averages method was applied for the creation of a dendrogram. A total of 344 reproducible, polymorphic markers were obtained. Unweighted pair group method using arithmetic averages clustering based on the Nei and Li coefficient of similarity separated the 101 genotypes into four distinct clusters. Analysis of molecular variance showed that 90% of the detected variation was found within the group, while the variation among groups contributed to only 10%. Our results indicate that the AFLP technique seemed to be a suitable molecular method for assessing genetic relationships between oilseed rape inbred lines with high levels of accuracy. Genetic similarity evaluated on the basis of AFLP molecular markers is a significant addition to classical methods of selection of parental components of winter oilseed rape hybrid varieties (e.g., 'Poznaniak').